Effects of temperature and pressure on the optical and vibrational properties of thermoelectric SnSe. Issue 17 (11th April 2019) - Efthimiopoulos, Ilias; Berg, Matthias; Bande, Annika; Puskar, Ljiljana; Ritter, Eglof; Xu, Wei; Marcelli, Augusto; Ortolani, Michele; Harms, Martin; Müller, Jan; Speziale, Sergio; Koch-Müller, Monika; et al.
Abstract : We have conducted a comprehensive investigation of the optical and vibrational properties of the binary semiconductor SnSe as a function of temperature and pressure by means of experimental and ab initio probes. Abstract : We have conducted a comprehensive investigation of the optical and vibrational properties of the binary semiconductor SnSe as a function of temperature and pressure by means of experimental and ab initio probes. Our high-temperature investigations at ambient pressure have successfully reproduced the progressive enhancement of the free carrier concentration upon approaching the Pnma → Bbmm transition, whereas the pressure-induced Pnma → Bbmm transformation at ambient temperature, accompanied by an electronic semiconductor → semi-metal transition, has been identified for bulk SnSe close to 10 GPa. Modeling of the Raman-active vibrations revealed that three-phonon anharmonic processes dominate the temperature-induced mode frequency evolution. In addition, SnSe was found to exhibit a pressure-induced enhancement of the Born effective charge. Such behavior is quite unique and cannot be rationalized within the proposed effective charge trends of binary materials under pressure.